Regulation of Tidal Flat Sediment Dynamics by an Ecological Submerged Breakwater: Insights from the Northern Coast of the Sheyang River Estuary, Jiangsu, China - Xiaofei Zhang; Aijun Wang; Xiang Ye; Wanqing Pang; Zhenkun Lin; Yanbin Fan (Journal of Marine Science and Engineering, 2026)
Tidal flats are shrinking and eroding due to sea-level rise and human activities. Ecological submerged breakwaters (ESBs) offer a novel solution combining coastal protection and ecological restoration, but their effects on sediment dynamics lack field evidence. This study presents synchronous in situ measurements from an inner tidal flat (WN01) and an outer shallow area (WN02) of a newly built riprap slope-type ESB on the northern coast of the Sheyang River Estuary, Jiangsu, China. Using Acoustic Doppler Velocimeters (ADVs) and wave-tide gauges, we examined hydrodynamics, suspended sediment concentration (SSC), bed shear stress, erosion–accretion, and sediment transport under normal-weather and strong wave events. Within the constraints of a 14-day observation at two stations, our results indicate that: (1) The ESB reduced wave height and weakened currents, shifting dominant bed shear stress from wave-dominated outside to tide-dominated inside. Under normal weather, both sides were accretive. (2) Strong wave events caused sharp increases in bed shear stress, net erosion on both sides, and a 2–3-fold SSC rise, breaking the normal balance. (3) Suspended sediment transport direction remained northwest inside during strong wave events but shifted to northeast/southeast outside, demonstrating effective isolation of wave-driven anomalies. Bedload was trapped inside, resulting in no net sediment loss, in contrast to the unprotected southern tidal flat. (4) We recommend moderately lowering the ESB crest elevation to prevent excessive accretion and implementing “grey-green” restoration (salt marshes or oyster reefs) to enhance coastal resilience against sea-level rise.